Upaya Peningkatan Compliance Quality Procedure SAP Plant Maintenance dengan Perbaikan Sistem Preventive Maintenance - Stevani Devita; Iwan Sahputra (Jurnal Titra, 2023)
The ISO Quality Procedure SAP Plant Maintenance document of the MaintenanceDepartment at PT. X has a gap percentage of 42% compared to the actual condition. The gapsinclude the implementation of Work Order for service operations and the Kitting Box program inPreventive Maintenance, which have not been carried out. This situation has caused the Preventive Maintenance business process to deviate from the standards, and the company's needs have not been met. This research aims to improve compliance with the ISO Quality Procedure SAP Plant Maintenance document, specifically in Preventive Maintenance, and fulfill thecompany's needs. The method used in this research is the implementation of system improvementin Preventive Maintenance with the help of Gap Analysis and Plan, Do, Check, Action (PDCA). The results of this research show that the implementation of improvement has been successfullycarried out. The audit checklist indicates that the Quality Procedure SAP Plant Maintenance has been fulfilled by 92%, with a final gap of 8%. The proposed suggestion is to continuously make improvements and supervise the implementation of those improvements. Additionally, the recruitment of a Planner position and coordination with the internal department can also be donepromptly so that other gaps can be addressed promptly.